On dissolution test for Hypertril tablets using high performance liquid chromatography - L. I. Kucherenko; N. V. Parniuk; Z. B. Moriak; L. H. Cherkovska; H. I. Tkachenko (Zaporozhye State Medical University, 2019)
Particular attention is paid to the release of the active ingredients of drugs in the form of tablets. Therefore, we have developed a method for determining the dissolution test, for the original drug Hypertril. The purpose. To develop a methodology for dissolution test for Hypertril tablets with an active substance content of 20 mg using the HPLC method. Materials and methods. In the studies we used Hypertril tablets with an active substance content of 20 mg, obtained in the Standardization and Drug Technology Laboratory at the Pharmaceutical Chemistry Department of ZSMU. A standard sample of the hypertril substance was received from the State Enterprise "Chemical Reagents Plant" (Kharkiv, Ukraine). We used high-performance liquid chromatograph Bishoff with an UV detector for studies. During the dissolution test of the Hypertril tablets, a device with a blade from the company Pharma Test PTWS 120D, Germany, was used. Results. As a result of the conducted studies, the chromatograms were obtained. Having analyzed the chromatograms, we proved that the method is highly sensitive and accurate and can be used to determine the dissolution test. The obtained study results showed that the amount of the active substance that passed into the solution from the Hypertril tablets after 45 minutes and is from 91.2 to 99.6 %, that meets the requirements of the State Pharmacopoeia of Ukraine. Conclusions. In the course of study, we developed a method for carrying out the dissolution test for Hypertril tablets with an active substance content of 20 mg using the HPLC method. The study results confirm that the developed method is accurate and reliable.